The Old Testament Library : Proverbs - Clifford, Richard J. (Louisville, Kentucky Westminster John Knox Press, 1999)
Through exacting translation, technical notes, and insightful commentary, Richard Clifford sheds new light on the book of Proverbs. He focuses on the rhetoric of Proverbs to demonstrate how the book fosters a lifelong search for wisdom and to enable readers to see how its instructions and maxims are concerned with contemporary issues. Clifford unveils the fascinating aspects of Proverbs - its wit and irony, honesty and profundity, drama and conflict, and, ultimately, its concern with wisdom as a fundamental option in life.
Introduction -- Date of composition and editing -- Historical context -- The wisdom literature that Proverbs inherited -- Distinctive ideas -- The background and function of personified wisdom and her rival -- The Hebrew text and versions of Proverbs -- The influence of Proverbs on later literature -- The meaning of Proverbs today -- Commentary -- 1:1-7 Introduction to the book -- 1:8-19 Lecture I: The deadly alternative to parental wisdom -- 1:20-33 Wisdom Poem I: The risk of spurning me -- 2:1-22 Lecture II: Seek wisdom and Yahweh will keep you safe -- 3:1-12 Lecture III
Includes bibliographical references (pages xiii-xvi) and index.
Keywords: Bible. -- Commentaries